Transitory increased blood pressure after upper airway surgery for snoring and sleep apnea correlates with the apnea-hypopnea respiratory disturbance index - Araújo,M.T.M. (2003)
A transitory increase in blood pressure (BP) is observed following upper airway surgery for obstructive sleep apnea syndrome but the mechanisms implicated are not yet well understood. The objective of the present study was to evaluate changes in BP and heart rate (HR) and putative factors after uvulopalatopharyngoplasty and septoplasty in normotensive snorers. Patients (N = 10) were instrumented for 24-h ambulatory BP monitoring, nocturnal respiratory monitoring and urinary catecholamine level evaluation one day before surgery and on the day of surgery. The influence of postsurgery pain was prevented by analgesic therapy as confirmed using a visual analog scale of pain. Compared with preoperative values, there was a significant (P < 0.05) increase in nighttime but not daytime systolic BP (119 ± 5 vs 107 ± 3 mmHg), diastolic BP (72 ± 4 vs 67 ± 2 mmHg), HR (67 ± 4 vs 57 ± 2 bpm), respiratory disturbance index (RDI) characterized by apnea-hypopnea (30 ± 10 vs 13 ± 4 events/h of sleep) and norepinephrine levels (22.0 ± 4.7 vs 11.0 ± 1.3 µg l-1 12 h-1) after surgery. A positive correlation was found between individual variations of BP and individual variations of RDI (r = 0.81, P < 0.01) but not between BP or RDI and catecholamines. The visual analog scale of pain showed similar stress levels on the day before and after surgery (6.0 ± 0.8 vs 5.0 ± 0.9 cm, respectively). These data strongly suggest that the cardiovascular changes observed in patients who underwent uvulopalatopharyngoplasty and septoplasty were due to the increased postoperative RDI.